Hypoglycemic effect of Parkia speciosa, Leucaena leucocephala and Laurus nobili in oral glucose-loaded rats / Siti Suhaila Harith ... [et al.] - Harith, Siti Suhaila; Hasbullah, Amirul Hafidz; Amat Sehab, Muhammad Shafiq Aqmal; Mohd Hassan, Mohd Shafiq (2013)
Traditional plants have been used as a cure for diabetes for a long time before the introduction of modern medicine. A few examples of plants that are commonly known for their hypoglycemic activity are Parkia speciosa (Petai), Leucaena leucocephala (Petai Belalang) and Laurus nobilis (Daun Selom). The society today does not aware the ability of these plants to prevent diabetes. The purpose of this experiment is to investigate the hypoglycemic effect of those three plants. Effects of daily feed of Parkia speciosa, Leucaena leucocephala and Laurus nobilis on (a) normal feed rats, (b) oral glucose-loaded rats, (c) oral glucose with Parkia speciosa extract-loaded rats, (d) oral glucose with Leucaena leucocephala extract-loaded rats, and (e) oral glucose with Laurus nobilis extract- loaded rats have been studied Results show that all of these traditional plants potentially reduced the blood glucose level of all rats with Parkia speciosa is the most effective followed by Laurus nobilis and Leucaena leucocephala.